2007
DOI: 10.1093/hmg/ddm181
|View full text |Cite
|
Sign up to set email alerts
|

Complexin 1 knockout mice exhibit marked deficits in social behaviours but appear to be cognitively normal

Abstract: Complexins are presynaptic proteins that modulate neurotransmitter release. Abnormal expression of complexin 1 (Cplx1) is seen in several neurodegenerative and psychiatric disorders in which disturbed social behaviour is commonplace. These include Parkinsons's disease, Alzheimer's disease, schizophrenia, major depressive illness and bipolar disorder. We wondered whether changes in Cplx1 expression contribute to the psychiatric components of the diseases in which Cplx1 is dysregulated. To investigate this, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…Moreover, clinical genetic studies have identified genes encoding presynaptic proteins as risk factors for schizophrenia (Karson et al, 1999; Mirnics et al, 2000; Tachikawa et al, 2001; Chen et al, 2004; Lee et al, 2005; Muller et al, 2005; Verma et al, 2005; Kirov et al, 2008; Sudhof, 2008; Walsh et al, 2008; Rujescu et al, 2009). Consistent with these findings, mutation of genes encoding presynaptic proteins has resulted in mouse models relevant to schizophrenia (Drew et al, 2007; Dyck et al, 2007, 2009; Etherton et al, 2009). Thus, we hypothesized that deletion or mutation of the presynaptic protein RIM1α, and its binding partners Rab3A and synaptotagmin, would lead to schizophrenia-related behavioural abnormalities (Powell and Miyakawa, 2006).…”
Section: Introductionsupporting
confidence: 54%
“…Moreover, clinical genetic studies have identified genes encoding presynaptic proteins as risk factors for schizophrenia (Karson et al, 1999; Mirnics et al, 2000; Tachikawa et al, 2001; Chen et al, 2004; Lee et al, 2005; Muller et al, 2005; Verma et al, 2005; Kirov et al, 2008; Sudhof, 2008; Walsh et al, 2008; Rujescu et al, 2009). Consistent with these findings, mutation of genes encoding presynaptic proteins has resulted in mouse models relevant to schizophrenia (Drew et al, 2007; Dyck et al, 2007, 2009; Etherton et al, 2009). Thus, we hypothesized that deletion or mutation of the presynaptic protein RIM1α, and its binding partners Rab3A and synaptotagmin, would lead to schizophrenia-related behavioural abnormalities (Powell and Miyakawa, 2006).…”
Section: Introductionsupporting
confidence: 54%
“…This non-preference for novelty was in contrast to other paradigms using a preference for novelty to assess object recognition and episodic memory in mice and rats [17,22,32,70]. Neophobia for novel food, objects, or locations has been well-documented in rodents (see [23,31]), and can be altered by pharmacological challenge [6,26,76], rearing conditions [28], or genetic change [3,18,38,45,57,62]. Nonpreference for novelty has been shown to be strain-dependent in mice [26,34].…”
Section: Discussionmentioning
confidence: 99%
“…Social defects are also common to many mutant mouse models of synaptic dysfunction or schizophrenia susceptibility genes (30,47,70). Surprisingly, during social novelty testing, Bdr mutants from stressed dams spent approximately the same time with the now familiar intruder mouse (Stranger 1) than the new intruder mouse (Stranger 2).…”
Section: Discussionmentioning
confidence: 99%